MESSENGER Observations of Fast Plasma Flows in Mercury's Magnetotail. Issue 19 (4th October 2018) - Dewey, Ryan M.; Raines, Jim M.; Sun, Weijie; Slavin, James A.; Poh, Gangkai
Abstract: We present the first observation of fast plasma flows in Mercury's magnetotail. Mercury experiences substorm activity phenomenologically similar to Earth's; however, field‐of‐view limitations of the Fast Imaging Plasma Spectrometer (FIPS) prevent the instrument from detecting fast flows in the plasma sheet. Although FIPS measures incomplete plasma distributions, subsonic flows impart an asymmetry on the partial plasma distribution, even if the flow directions are outside the field of view. We combine FIPS observations from 387 intervals containing magnetic field dipolarizations to mitigate these instrument limitations. By taking advantage of variations in spacecraft pointing during these intervals, we construct composite plasma distributions from which mean flows are determined. We find that dipolarizations at Mercury are embedded within fast sunward flows with an averaged speed of 300 km/s compared to a typical background flow of 50 km/s. Plain Language Summary: Similar to Earth, Mercury has a global magnetic field that forms a protective cavity, known as the magnetosphere, within the solar wind. The solar wind compresses the dayside magnetosphere, while stretching the nightside magnetosphere behind the planet. Variations within the solar wind cause dynamic activity within Mercury's magnetosphere, with a process known as magnetic reconnection mediating the interaction. Magnetic reconnection changes the topology of magnetic field lines and transfers energy and momentum from the magnetic field to the plasma within it. At Earth, magnetic reconnection in the nightside magnetosphere drives fast flows of plasma toward the planet, which when nearing the planet are slowed and diverted. These flows cannot be identified directly at Mercury because of limitations of the MESSENGER spacecraft measurements collected there. This research paper develops a new statistical technique to identify and characterize these fast flows at Mercury. Key Points: Multiple FIPS plasma observations from the MESSENGER spacecraft have been combined statistically to determine average flows Observations collected during dipolarizations produce an average plasma flow of 300 km/s compared to 50 km/s during background intervals Several dipolarizations are required to unload Mercury's magnetotail during a substorm, and some flows may reach the planet's surface